# 3. The Circle

### Also on this page:

## a. Circle Formulas

### Center at the Origin

The circle with centre (0, 0) and radius *r* has the equation:

x^{2}+y^{2}=r^{2}

This means any point (*x*, *y*) on the circle will give the radius squared when substituted into the circle equation.

### Center not at the Origin

The circle with centre (*h*, *k*) and radius *r* has the equation:

(

x−h)^{2}+ (y−k)^{2}=r^{2}

These formulas are a direct result of Pythagoras' Formula for the length of the hypotenuse of a right triangle.

### Need Graph Paper?

### Example 1

Sketch the circle *x*^{2} + *y*^{2} = 4.

Find the center and radius first.

Answer

The equation is in the form *x*^{2} + *y*^{2} = *r*^{2}, so we have a circle, center (0, 0) with radius `r=sqrt4=2`.

Easy to understand math videos:

MathTutorDVD.com

### Example 2

Sketch the circle (*x* − 2)^{2} + (*y* − 3)^{2} = 16

Find the center and radius first.

Answer

The equation is in the form (*x* − *h*)^{2} + (*y* − *k*)^{2} = *r*^{2}, so we have a circle with centre at (2, 3) and the radius is `r=sqrt(16)=4`.

Please support IntMath!

### Example 3

Sketch the circle (*x* + 4)^{2} + (*y* − 5)^{2} = 36

Answer

The equation is in the form (*x* − *h*)^{2} + (*y* − *k*)^{2} = *r*^{2}.

We have a circle with centre at (−4, 5) and the radius is `r=sqrt(36)=6`.

Be careful with **positive **and **negative** *x*- and *y*-values in this work!

Please support IntMath!

## b. The General Form of the Circle

An equation which can be written in the following form (with constants *D*,* E*,* F*) represents a **circle**:

x^{2}+y^{2}+Dx + Ey + F= 0

This is called the **general form of the circle**.

### Example 4

Find the centre and radius of the circle

x^{2}+y^{2}+ 8x+ 6y= 0

Sketch the circle.

Answer

Please revise **Completing
the Square** first...

Our aim is to get the equation into the form: (*x* − *h*)^{2} + (*y* − *k*)^{2} = *r*^{2}

We complete the square on the *x*-related portion and on the *y*-related portion, at the same time.

`x^2+y^2+8x+6y=0`

Group the *x* parts together and the *y* parts togther:

`(x^2+8x)+(y^2+6y)=0`

Complete the square on each of the *x* and *y* parts.

`(x^2+8x+16)+(y^2+6y+9)` `=16+9` `=25`

`(x+4)^2+(y+3)^2=5^2`

This is now in the format we require and we can determine the center and radius of the circle.

So the centre of the circle is (−4, −3) and the radius is 5 units.

Note that the circle passes through (0, 0). This is logical, since:

- The circle has radius 5
- Considering the right triangle formed by the points (−4, −3), (0, −3), and (0, 0), we can apply Pythagoras' Theorem and obtain: (−4)
^{2}+ (−3)^{2}= (5)^{2} - The formula for a circle follows from Pythagoras' Theorem.

Easy to understand math videos:

MathTutorDVD.com

### Exercises

1. Find the equation of the circle with centre `(3/2, -2)` and radius `5/2`.

Answer

Centre `(3/2, -2)` radius `5/2`.

General form of the equation of a circle:

`(x-h)^2+(y-k)^2=r^2`

The required equation for this case:

`(x-3/2)^2+(y-(-2))^2=(5/2)^2`

`(x-3/2)^2+(y+2)^2=(5/2)^2`

There is no need to expand this out, since this is the most useful form of the equation.

Get the Daily Math Tweet!

IntMath on Twitter

2. Determine the centre and radius and then sketch the circle:

3

x^{2}+ 3y^{2}− 12x+ 4 = 0

Answer

We **complete the square** as we did in an earlier example above.

First, we collect the *x* parts together and the *y* parts together, then divide throughout by 3.

`3x^2+3y^2-12x+4=0`

`3x^2-12x+3y^2+4=0`

`x^2-4x+y^2+4/3=0`

Then we complete the square on the *x* part. We do not need to do so for the *y* part because there is no single *y* term (only a *y*^{2} term).

`(x^2-4x+4)+y^2+4/3=4`

`(x-2)^2+y^2=4-4/3`

`(x-2)^2+y^2=8/3`

So the circle has centre `(2,0)` and has radius `sqrt(8/3)~~1.63`.

Get the Daily Math Tweet!

IntMath on Twitter

3. Find the points of intersection of the circle

x^{2}+y^{2}−x− 3y= 0

with the line

y=x− 1.

Answer

We solve the 2 equations simultaneously by substituting the expression

`y = x -1`

into the expression

`x^2+y^2-x-3y=0`

[See some background to this at: Algebraic Solution of Systems of Equations.]

We have:

`x^2+(x-1)^2-x-3(x-1)=0`

`x^2+x^2-2x+1-x-3x+3=0`

`2x^2-6x+4=0`

`x^2-3x+2=0`

`(x-1)(x-2)=0`

So we see that the solutions for *x* are `x = 1` or `x = 2`. This gives the corresponding y-values of `y = 0` and `y = 1`.

So the points of intersection are at: `(1, 0)` and `(2, 1)`.

We can see that our answer is correct in a sketch of the situation:

### Exercise for You

Where did (0.5, 1.5) for the center of the circle come from?

Easy to understand math videos:

MathTutorDVD.com

### Conic section: Circle

How can we obtain a circle from slicing a cone?

Each of the lines and curves in this chapter are **conic sections**, which means the curves are formed when we slice a cone at a certain angle.

If we slice a cone with a plane at right angles to the axis of the cone, the shape formed is a circle.

### Search IntMath, blog and Forum

### Online Math Solver

This math solver can solve a wide range of math problems.

Go to: Online algebra solver

### Math Lessons on DVD

Math videos by MathTutorDVD.com

Easy to understand math lessons on DVD. See samples before you commit.

More info: Math videos

### The IntMath Newsletter

Sign up for the free **IntMath Newsletter**. Get math study tips, information, news and updates each fortnight. Join thousands of satisfied students, teachers and parents!